Instilling Ulu al-Albâb Values ‘Spiritual Depth’ Through Conversational Texts in the Al-‘Arabiya li al-Hayâh Book - Kirom, Makhiulil; Qomari, Nur; Bakhiet, Bakri Mohommed (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
Character is a reflection of the person; positive character reflects the positive values that one possesses. The attempt to teach this positive character continues through al- ‘Arabiyah's li Hayâh textbook, which claims to contain the values of Ulu al-Albâb. This research aims to analyze the Ulu al-Albâb values contained in the text of the textbook's conversation and discuss them in depth. The al-‘Arabiya li al-Hayâh book became the primary source of learning for students at one of the universities in East Java. This research uses a qualitative research method with a descriptive analysis by Harold D. Lasswell's approach to the al-‘Arabiya li al-Hayâh textbook 1st volume. The analysis is carried out systematically, objectively, and qualitatively. The analysis's findings demonstrate that Ulu al-Albâb 's values are distributed pretty equally across the textbook. It is seen from the text of the conversation that it contains spiritual values evenly and is designed to instill those values in the student's subconscious. This research contributes to the understanding of character development through Arabic textbooks. The results of this research can be beneficial to the developers, teachers, and Arabic language learners to instill the spiritual depth values of Ulu al-Albâb.